Mechanical properties of TiB/Ti-6Al-4V alloy composites fabricated by spark plasma sintering - Hiroshi IZUI (The Japan Society of Mechanical Engineers, 2017)
Ti-6Al-4V alloy exhibits a good combination of excellent properties, such as high specific strength, high fatigue strength, good ductility and weldability. However, Ti-6Al-4V alloy shows low stiffness and poor wear resistance. To further increase the strength properties and improve the stiffness and wear resistance, TiB reinforced Ti-6Al-4V alloy matrix (TiB/Ti-6Al-4V) composites were fabricated by a spark plasma sintering (SPS) process. The TiB/Ti-6Al-4V alloy composites with 4.2 vol.% TiB, which were fabricated at a sintering temperature of 900 °C and for a holding time of 30 min, had the highest tensile strength of 1174 MPa. The Young’s modulus and Vickers microhardness of the composites increased with increasing TiB volume fraction, and the composite with 16.7 vol.% TiB exhibited values of 159 GPa and 517 HV, respectively. The tensile strength of the composite with 4.2 vol.% TiB at 400 °C was higher than that of the mild annealed Ti-6Al-4V alloy. The fatigue limits (over 107 cycles) at room temperature and 600 °C of the composites with 4.2 vol.% TiB were 350 MPa and 200 MPa, respectively. The creep strains at room temperature of the composites with 1.4 and 4.2 vol.% TiB did not increase with increasing creep time.